Pengaruh Tingkat Suku Bunga, Nilai Tukar, Inflasi dan Return on Assets (ROA) terhadap Harga Saham pada Sub-Sektor Perbankan Di Bursa Efek Indonesia Tahun 2016-2019 - Jessica Jessica; Michelle Michelle; Wirda Lilia (Universitas Batanghari Jambi, 2021)
This research has a purpose of knowing the effect of Interest Rate, Exchange Rate, Inflation, and Return OnAsset. Against the Share Price on Banking Sub-Sector in Indonesia Stock Exchange period 2016-2019. The Data used is source by financial data in Indonesia Stock Exchange through www.idx.co.id, and has been selected based on predetermined criteria. Population used in this research is bank companies which is 46 companies. We used purposive sample, so the sample was 15 companies. With this research, it is hoped that it can become a science to help the next researcher and also college student or general public who need information. In this research, we know that Return On Asset is partially influential and significant with share price. Interest rate, exchange rate, inflation partially has no effect and not significant with share price on Banking Sub-Sector. But all the variables effect simultaneously. Selection of sector in this research is because Indonesia has been more advanced era of globalization, of course there will be many foreigners nor a local who will need various kinds of basic needs, so many companies built because of that basis. That’s why we intend to research this topic.